Protocol for the development of a CONSORT-equity guideline to improve reporting of health equity in randomized trials. (December 2015) - Welch, Vivian; Jull, J.; Petkovic, J.; Armstrong, R.; Boyer, Y.; Cuervo, LG; Edwards, SJL; Lydiatt, A.; Gough, D.; Grimshaw, J.; Kristjansson, E.; Mbuagbaw, L.; et al.
Abstract Background Health equity concerns the absence of avoidable and unfair differences in health. Randomized controlled trials (RCTs) can provide evidence about the impact of an intervention on health equity for specific disadvantaged populations or in general populations; this is important for equity-focused decision-making. Previous work has identified a lack of adequate reporting guidelines for assessing health equity in RCTs. The objective of this study is to develop guidelines to improve the reporting of health equity considerations in RCTs, as an extension of the Consolidated Standards of Reporting Trials (CONSORT). Methods/design A six-phase study using integrated knowledge translation governed by a study executive and advisory board will assemble empirical evidence to inform the CONSORT-equity extension. To create the guideline, the following steps are proposed: (1) develop a conceptual framework for identifying "equity-relevant trials, " (2) assess empirical evidence regarding reporting of equity-relevant trials, (3) consult with global methods and content experts on how to improve reporting of health equity in RCTs, (4) collect broad feedback and prioritize items needed to improve reporting of health equity in RCTs, (5) establish consensus on the CONSORT-equity extension: the guideline for equity-relevant trials, and (6) broadly disseminate and implement the CONSORT-equity extension. Discussion This work will be relevant to a broad range of RCTs addressing questions of effectiveness for strategies to improve practice and policy in the areas of social determinants of health, clinical care, health systems, public health, and international development, where health and/or access to health care is a primary outcome. The outcomes include a reporting guideline (CONSORT-equity extension) for equity-relevant RCTs and a knowledge translation strategy to broadly encourage its uptake and use by journal editors, authors, and funding agencies.